From diagnosis to long-term management: the experiences of older New Zealanders with obstructive sleep apnoea - Gibson R; Campbell A; Mather S; Neil A (Royal New Zealand College of General Practitioners)
INTRODUCTION: In New Zealand (NZ), access to public sleep services is limited to people deemed with the highest need. The prevalence of obstructive sleep apnoea (OSA) increases with age, but the symptoms and the treatment pathway is expected to differ for older compared to younger patients. This study explored the experience of older people regarding diagnosis and treatment services for OSA in order to inform considerations required in primary health and sleep services. METHODS: Patients who were initiated on Continuous Positive Airway Pressure (CPAP) therapy at the age of 65 years or older were invited to one of three 1.5-h focus group discussions. In total, 16 patients attended; nine were accompanied by their spouse or partner. Discussions were semi-structured and explored experiences with the OSA pathway, from diagnosis through to long-term management. RESULTS: Thematic analysis highlights the key symptoms of OSA. Patients’ experiences with diagnostic and treatment services were generally positive. However, there was an overarching need for greater knowledge and follow up regarding OSA and CPAP therapy. Most patients were happy with CPAP treatment. Issues associated with long-term use, comfort and daily management were highlighted, and strategies used to overcome them discussed. DISCUSSION: Focus groups reported similar experiences, positively endorsing the health value of OSA diagnosis and CPAP therapy. Mechanisms and resources are required at a primary healthcare level in order to raise awareness around sleep and aging, OSA and CPAP. This would aid earlier and more appropriate diagnosis and management of OSA and help overcome some of the gaps identified in this study.
Keywords: Aged; Aged, 80 and over; Comorbidity; Continuous Positive Airway Pressure; Female; Focus Groups; Humans; Male; New Zealand; Patient Compliance; Patient Satisfaction; Prevalence; Sleep Apnea, Obstructive; Socioeconomic Factors; 1110 Nursing; 1117 Public Health and Health Services